Exposure‐Response Relationships in Patients With HER2‐Positive Metastatic Breast Cancer and Other Solid Tumors Treated With Trastuzumab Deruxtecan. Issue 4 (10th June 2021) - Yin, Ophelia; Iwata, Hiroji; Lin, Chia‐Chi; Tamura, Kenji; Watanabe, Junichiro; Wada, Russ; Kastrissios, Helen; AbuTarif, Malaz; Garimella, Tushar; Lee, Caleb; Zhang, Lin; Shahidi, Javad; et al.
Abstract : Trastuzumab deruxtecan (T‐DXd) is a HER2‐targeting antibody‐drug conjugate composed of a novel enzyme‐cleavable linker and membrane‐permeable topoisomerase I inhibitor payload. T‐DXd has been approved for HER2‐positive metastatic breast cancer and for HER2‐positive metastatic gastric cancer. The approval in breast cancer was based on results from the DESTINY‐Breast01 (U201; NCT03248492) and J101 (NCT02564900) trials. Here, we present dose justification for the approved 5.4 mg/kg every‐3‐weeks (Q3W) dose based on exposure‐efficacy evaluated in patients with HER2‐positive breast cancer ( N = 337) from these 2 trials. Exposure‐safety was assessed in patients with all tumor types ( N = 639, n = 512 with breast cancer) across 5 trials, including J101 and DESTINY‐Breast01. T‐DXd doses ranged from 0.8–8.0 mg/kg Q3W; most patients received 5.4 ( n = 312) or 6.4 mg/kg ( n = 291). For each end point, multivariate logistic or Cox regression analysis was performed using various exposure metrics of T‐DXd and released drug. A statistically significant association was observed between intact T‐DXd area under the concentration‐time curve (AUC) and confirmed objective response rate (ORR; P = 0.028). No significant exposure‐response relationships were observed between intact T‐DXd or released drug and duration of response or progression‐free survival; however, follow‐up was limited. All evaluated safety end points demonstrated a significant ( P < 0.05) relationship with either intact T‐DXd or released drug, with higher adverse event (AE) rates projected at higher exposures. Dose‐response projections suggested an increase in ORR (67.5% vs. 62.9%) and toxicity (e.g., grade ≥ 3 all‐cause treatment‐emergent AEs: 61% vs. 54%) with T‐DXd 6.4 vs. 5.4 mg/kg. Results demonstrate the benefit‐risk profile at different doses and guide clinicians in the use of the 5.4‐mg/kg Q3W dose in patients with HER2‐positive metastatic breast cancer.